APLP1 is a synaptic cell adhesion molecule, supporting maintenance of dendritic spines and basal synaptic transmission - Schilling, Sandra; Mehr, Annika; Müller, Ulrike C. (The journal of neuroscience, 2017)
The amyloid precursor protein (APP), a key player in Alzheimer's disease, belongs to the family of synaptic adhesion molecules (SAMs) due to its impact on synapse formation and synaptic plasticity. These functions are mediated by both the secreted APP ectodomain that acts as a neurotrophic factor and full-length APP forming trans-cellular dimers. Two homologs of APP exist in mammals: the APP like proteins APLP1 and APLP2, exhibiting functions that partly overlap with those of APP. Here we tested whether APLP1 and APLP2 also show features of SAMs. We found that all three family members were upregulated during postnatal development coinciding with synaptogenesis. We observed presynaptic and postsynaptic localization of all APP family members and could show that heterologous expression of APLP1 or APLP2 in non-neuronal cells induces presynaptic differentiation in contacting axons of cocultured neurons, similar to APP and other SAMs. Moreover, APP/APLPs all bind to synaptic-signaling molecules, such as MINT/X11. Furthermore, we report that aged APLP1 knock-out mice show impaired basal transmission and a reduced mEPSC frequency, likely resulting from reduced spine density. This demonstrates an essential nonredundant function of APLP1 at the synapse. Compared to APP, APLP1 exhibits increased trans-cellular binding and elevated cell-surface levels due to reduced endocytosis. In conclusion, our results establish that APLPs show typical features of SAMs and indicate that increased surface expression, as observed for APLP1, is essential for proper synapse formation in vitro and synapse maintenance in vivo. SIGNIFICANCE STATEMENT According to the amyloid-cascade hypothesis, Alzheimer's disease is caused by the accumulation of Aβ peptides derived from sequential cleavage of the amyloid precursor protein (APP) by β-site APP cleaving enzyme 1 (BACE1) and γ-secretase. Here we show that all mammalian APP family members (APP, APLP1, and APLP2) exhibit synaptogenic activity, involving trans-synaptic dimerization, similar to other synaptic cell adhesion molecules, such as Neuroligin/Neurexin. Importantly, our study revealed that the loss of APLP1, which is one of the major substrates of BACE1, causes reduced spine density in aged mice. Because some therapeutic interventions target APP processing (e.g., BACE inhibitors), those strategies may alter APP/APLP physiological function. This should be taken into account for the development of pharmaceutical treatments of Alzheimer's disease.
Gesehen am 07.05.2018